The effects of a learning management model using design thinking and community-based learning to enhance local visual art design in line with the creative economy concept among high school students - Suwan, Saran; Sithsungnoen, Chanasith (Humanities, Arts and Social Sciences Studies, 2025)
This research aims to 1) develop and evaluate the quality of a learning management model using design thinking and community-based learning to enhance local visual art design in line with the creative economy concept among high school students, 2) study the visual art designing skill process, 3) study local art projects following the creative economy concept, and 4) study students’ opinions towards the learning management model and the value of art to the community. Purposive sampling was conducted for this research, consisting of 16 high school students from Koh Kret Creative Art Club at a secondary school in Nonthaburi province in the academic year 2023. The method used in this research is research and development (R&D). Research instruments included: 1) a learning management model, 2) four lesson plans, 3) evaluation forms for the visual art design skill process, 4) evaluation forms for local art projects following the creative economy concept, and 5) questionnaires for student opinions. The data analysis was conducted by using mean (M), standard deviation (SD), and content analysis. The results show that the learning management model consisted of five components: (1) principles, (2) objectives, (3) a learning process consisting of four stages as follows: 1) Perceive (P), which includes 1.1 Community Planning Survey (CPS), 1.2 Community Learning (CL), and 1.3 Community Reflection (CR), 2) Producing Ideas (P), 3) Prototype (P), and 4) Proof (P) which includes Community Evaluation (CE). (4) measurement and evaluation, and (5) success conditions. The learning management model was evaluated by experts and it was found that, 1) the appropriateness was at the highest level (M = 4.69, SD = 0.45), 2) the visual art design skill process reflected a very good level (M = 2.61, SD = 0.48), 3) local art projects following the creative economy concept reflected a very good level (M = 2.55, SD = 0.39), and 4) student opinions toward the learning management model and the value of art in the community were at the highest level (M = 4.66, SD = 0.56).